PERANCANGAN SISTEM INFORMASI KETERSEDIAAN OBAT DI GUDANG FARMASI PEKAN LABUHAN DINAS KESEHATAN KOTA MEDAN TAHUN 2014 - LESTARI HARIATY SIMANJUNTAK; Ria Masniari Lubis; Abdul Jalil Amri Arma (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Pharmacy store Pekan Labuhan of Medan Health Office is a technical implementation unit manager of the medicine in the Medan Health Office were instrumental in ensuring the availability of medicine in the region of Medan Health Office. Implementation of management informations system medicine of Pharmacy Store Pekan Labuhan of Medan Health Office refers to existing systems that is based on the Report of Medicine and Demand then processed manually and partly by a computer. Due still use the manual way to manage the availability of medicine informations systems, so sometimes the information generated is less accurate, relevant and timely. This in certainly a very impact on the efficiency an effectiveness of the medicine availability informations. The goal of designing this system is to have medicine control management that can process the data and produce the information of the good medicine availability for supporting the medicine programme management and health supply in Pharmacy Store Pekan Labuhan of Medan Health Office. The design of this system uses system development life cycle. This life cycle has several stages. They are planning stage, analysing stage, designing stage, testing stage and keeping stage. The result of designing this system is the report of the medicine availability, medicine entry and out as of the date, month, year and donors. After doing this research, there is a suggestion that can be applied in Pharmacy Store Pekan Labuhan of Medan Health Office. It is to develop the system to be a client server information system. It is needed some trainings for administrators and operators of the new system to have the accuracy in inputting the data. Keywords : System, information, availability medicine information, computer program.